A phase I clinical study of immunotherapy for advanced colorectal cancers using carcinoembryonic antigen-pulsed dendritic cells mixed with tetanus toxoid and subsequent IL-2 treatment. Issue 1 (December 2016) - Liu, Ko-Jiunn; Chao, Tsu-Yi; Chang, Jang-Yang; Cheng, Ann-Lii; Ch'ang, Hui-Ju; Kao, Woei-Yau; Wu, Yu-Chen; Yu, Wei-Lan; Chung, Tsai-Rong; Whang-Peng, Jacqueline
Abstract Background To better evaluate and improve the efficacy of dendritic cell (DC)-based cancer immunotherapy, we conducted a clinical study of patients with advanced colorectal cancer using carcinoembryonic antigen (CEA)-pulsed DCs mixed with tetanus toxoid and subsequent interleukin-2 treatment. The tetanus toxoid in the vaccine preparation serves as an adjuvant and provides a non-tumor specific immune response to enhance vaccine efficacy. The aims of this study were to (1) evaluate the toxicity of this treatment, (2) observe the clinical responses of vaccinated patients, and (3) investigate the immune responses of patients against CEA before and after treatment. Methods Twelve patients were recruited and treated in this phase I clinical study. These patients all had metastatic colorectal cancer and failed standard chemotherapy. We first subcutaneously immunized patients with metastatic colorectal cancer with 1 × 106 CEA-pulsed DCs mixed with tetanus toxoid as an adjuvant. Patients received 3 successive injections with 1 × 106 CEA-pulsed DCs alone. Low-dose interleukin-2 was administered subcutaneously following the final DC vaccination to boost the growth of T cells. Patients were evaluated for adverse event and clinical status. Blood samples collected before, during, and after treatment were analyzed for T cell proliferation responses against CEA. Results No severe treatment-related side effects or toxicity was observed in patients who received the regular 4 DC vaccine injections. Two patients had stable disease and 10 patients showed disease progression. A statistically significant increase in proliferation against CEA by T cells collected after vaccination was observed in 2 of 9 patients. Conclusions The results of this study indicate that it is feasible and safe to treat colorectal cancer patients using this protocol. An increase in the anti-CEA immune response and a clinical benefit was observed in a small fraction of patients. This treatment protocol should be further evaluated in additional colorectal cancer patients with modifications to enhance T cell responses. Trial registration ClinicalTrials.gov (identifierNCT00154713 ), September 8, 2005